Dexamethasone Acetate Nanocrystals, Characterization and Dissolution Studies in Presence of Polymorphic Phases - Bastos, Flavia Lemos Ayres da Gama [UNESP]; Barbosa, Thúlio Wliandon Lemos [UNESP]; da Silva, Bruna Lallo [UNESP]; Oshiro Junior, João Augusto [UNESP]; Chiavacci, Leila Aparecida [UNESP] (Bentham Science Publishers, 2023)
Background: A drug with poor water-solubility, like Dexamethasone acetate, can present lower bioavailability conventional for pharmaceutical formulations, and the presence of polymorphs in the raw material can lead to drug quality problems. Objective: In this study, nanocrystals of dexamethasone acetate were synthesized by high pressure ho-mogenizer (HPH) method in surfactant poloxamer 188 (P188) solid dispersion and the bioavailable in raw material with polymorphism presence was evaluated. Methods: The powder pre-suspension was prepared by the HPH process, and the nanoparticles formed were incorporated in P188 solutions. The nanocrystals formed were characterized by techniques of XRD, SEM, FTIR, thermal analysis by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), dynamic light scattering (DLS) to analyze the particle size and zeta potential, and in vitro evaluation by dissolution studies. Results: The characterization techniques were adequate to show the presence of raw material with physical moisture between two dexamethasone acetate polymorphs. The nanocrystals formed in the presence of the P188 in the formulation showed a considerable increase in the rate of dissolution of the drug in the medium and in the size of the stable nanocrystals, even in the presence of dexamethasone acetate polymorphs. Conclusion: The results showed that it was possible to produce dexamethasone nanocrystals by HPH process with regular size by the presence of the small amount of P188 surfactant. This article presents a novelty in the development of dexamethasone nanoparticles that have different polymorphic forms in their physical composition.
Keywords: bioavailability; Dexamethasone acetate; dissolution; nanocrystal; pharmaceutical formulations; polymorphism